2007
DOI: 10.1634/stemcells.2007-0177
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Signaling Promotes Proliferation of Progenitor Cells in the Adult Mouse Subventricular Zone

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
209
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 228 publications
(228 citation statements)
references
References 59 publications
17
209
1
1
Order By: Relevance
“…β-catenin pathway, also known as canonical Wnt pathway or β-catenin/TCF pathway, mediates cell proliferation by regulating cyclin D1 expression (Shtutman et al, 1999;Tetsu et al, 1999). In addition, recent studies including ours have shown that GSK-3β and β-catenin pathway are involved in the proliferation of neural precursor cells in both embryo and adult brains (Lie et al, 2005;Adachi et al, 2007;Hirsch et al, 2007;Boku et al, 2009). These results of studies suggest that bFGF might regulate proliferation of neural precursor cells through GSK-3β and β-catenin pathway.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…β-catenin pathway, also known as canonical Wnt pathway or β-catenin/TCF pathway, mediates cell proliferation by regulating cyclin D1 expression (Shtutman et al, 1999;Tetsu et al, 1999). In addition, recent studies including ours have shown that GSK-3β and β-catenin pathway are involved in the proliferation of neural precursor cells in both embryo and adult brains (Lie et al, 2005;Adachi et al, 2007;Hirsch et al, 2007;Boku et al, 2009). These results of studies suggest that bFGF might regulate proliferation of neural precursor cells through GSK-3β and β-catenin pathway.…”
Section: Introductionmentioning
confidence: 78%
“…β-catenin pathway is involved in regulating the proliferation of neural precursor cells both in embryo and adult brain (Lie et al, 2005;Adachi et al, 2007;Hirsch et al, 2007;Boku et al, 2009). Therefore, we hypothesized that ROCK regulates bFGF-induced proliferation of SH-SY5Y cells through β-catenin pathway.…”
Section: Consequently Sh-sy5y Cells May Fulfill the Definitions Of Nmentioning
confidence: 99%
“…Numerous studies have also reported roles for Wnt signaling in the SVZ. -catenin-responsive cells exist in the SVZ throughout the development of the CNS [140], and their activation promotes progenitor cell proliferation [141]. Activation of -catenin signaling increases the numbers of oligodendrocytes derived from this neurogenic site, while inhibition seems to reduce the glial cell number [142].…”
Section: Wnt Signaling and Adult Neurogenesis: Intracellular Componentsmentioning
confidence: 99%
“…26 The injection of a retrovirus carrying a constitutively active form of β-catenin or a highly selective GSK3β inhibitor, both of which activate Wnt/β-catenin signaling, increased the proliferation of transit-amplifying cells, which ultimately led to an increased number of new neurons in the OB. These results indicated that Wnt/β-catenin signaling positively regulates the proliferation of neuronal progenitors in the adult SVZ (Fig.…”
Section: Neural Stem Cells In the Subventricular Zonementioning
confidence: 99%